EAAT2 as a therapeutic research target in Alzheimer's disease: A systematic review - Wood, Oliver W. G.; Yeung, Jason H. Y.; Faull, Richard L. M.; Kwakowsky, Andrea (Frontiers in Neuroscience, 2022)
Glutamate is the main excitatory neurotransmitter in the human central nervous system, responsible for a wide variety of normal physiological processes. Glutamatergic metabolism and its sequestration are tightly regulated in the normal human brain, and it has been demonstrated that dysregulation of the glutamatergic system can have wide-ranging effects both in acute brain injury and neurodegenerative diseases. The excitatory amino acid transporter 2 (EAAT2) is the dominant glutamatergic transporter in the human brain, responsible for efficient removal of glutamate from the synaptic cleft for recycling within glial cells. As such, it has a key role in maintaining excitatory-inhibitory homeostasis. Animal studies have demonstrated dysregulation or alterations of EAAT2 can have implications in neurodegenerative disorders. Despite extensive research into glutamatergic alterations in AD mouse models, there is a lack of studies examining the expression of EAAT2 within the AD human brain. In this systematic review, 29 articles were identified that either analyzed EAAT2 expression in the AD human brain or used a human-derived cell culture. Studies were inconclusive as to whether EAAT2 was upregulated or downregulated in AD. However, changes in localization and correlation between EAAT2 expression and symptomatology was noted. These findings implicate EAAT2 alterations as a key process in AD progression and highlight the need for further research into the characterization of EAAT2 processes in normal physiology and disease in human tissue and to identify compounds that can act as EAAT2 neuromodulators.